Des murs et des hommes : réflexions sur la définition des communautés italiques - Lucas Aniceto (Frontière·s)
Lucania and Apulia offer a fascinating laboratory for studying indigenous urban phenomena during the Hellenistic period. The complex urban settlements that appear in this area constitute the core of hierarchically and institutionally well-structured civic communities. The fortification plays an essential role: as a landmark and a collective building, it contributes to the definition of these nucleated settlements. Through two major case studies, we will explore the societal value of these fortifications, that is how they reflect and help define a social fabric. Through the distribution of necropolises, we will try to understand to what extent a fortification delimits an urban space. Then, we will focus on the ‘acropolis’ and its inhabitants in order to address the principles of internal division inherent to these communities. Overall, we will seek to highlight the elite’s practices and their use of urban space as a way to assert their prestige within their respective communities.